Social Order and Conflict: Compared Methodology Outcomes un Nine Localities of Colombia - García, Clara Inés; Guzmán, Álvaro; Aramburo, Clara Inés; Rodríguez, Alba Nubia; Domínguez, Juan Camilo (Sociedad y Economía, 2014)
The article depicts the use of a compared methodology and its application to the analysisof the reconfiguration of nine local orders. All of them located in zones of very acute armedconflicts in Colombia. We use Historic Sociology and specially Charles Ragin’s proposal,and base the work in the comparative case study approach. We identify differentkinds of local orders, and similarities between the orders forming a same kind of order,as well as the differences between various local orders and the comparison of reconfi-guration paths observed during the armed conflict. We conclude with a general thoughtrelated to the adhesion to the principles of complexity and causal heterogeneity appliedto the relations between civilian actions and the coercion of armed groups.